Partially bio-based furyl-functionalized organosoluble poly(ether ether ketone)s - Kuhire, Sachin S.; Talanikar, Aniket A.; Tawade, V, Bhausaheb; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (Polymer International, 2021)
A new series of partially bio-based (co)poly(ether ether ketone)s bearing pendent furyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar proportions of 4,4 `-(furan-2-ylmethylene)bis(2-methoxyphenol) and bisphenol-A with 4,4 `-difluorobenzophenone. The chemical structures, compositions and random nature of (co)poly(ether ether ketone)s were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of the (co)poly(ether ether ketone)s were in the range 0.74-2.90 dL g(-1) and 33 500-46 300 g mol(-1), respectively, indicating the formation of reasonably high molecular weight polymers. (Co)poly(ether ether ketone)s were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether ether ketone)s exhibited 10% weight loss and glass transition temperatures in the range 429-464 and 152-156 degrees C, respectively. A representative copoly(ether ether ketone) was crosslinked with 1,1 `-(methylenedi-1,4-phenylene)bismaleimide via Diels-Alder reaction to form a crosslinked polymer which showed improved mechanical properties and was recycled twice without significant loss of mechanical properties. Diels-Alder/retro Diels-Alder reaction was demonstrated by studies of sol-gel transformation, solubility tests, DSC and stress-strain measurements. (c) 2020 Society of Chemical Industry
Keywords: aromatic poly(ether ether ketone)s; bio-based; crosslinking; Diels-Alder reaction; pendent furyl groups

Pendant propargyloxy-functionalized aromatic (co)polycarbonates: synthesis, thermal crosslinking and chemical modification - Nagane, Samadhan S.; Maher, Deepak M.; Verma, Savita; Talanikar, Aniket A.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2022)
A bisphenol monomer bearing pendant propargyloxy group viz, 1, 1-bis (4-hydoxyphenyl)-1-(4 `-propargyloxyphenyl) ethane (BPP) was synthesized starting from commercially available 1, 1, 1-tris (4-hydroxyphenyl) ethane (THPE) by mono O-propargylation reaction using propargyl bromide. A new series of pendant propargyloxy-functionalized aromatic (co)polycarbonates was synthesized by low-temperature solution polycondensation of BPP or different molar ratios of BPP and bisphenol-A with triphosgene in dichloromethane in the presence of triethylamine. The formation of reasonably high molecular weight (co)polycarbonates was confirmed by inherent viscosity (0.52-0.83 dL/g) and gel permeation chromatography (M-n 37,000-69,800 g/mol, polystyrene standards) measurements. C-13 NMR spectral studies supported formation of random copolycarbonates in copolymerization of BPP and BPA with triphosgene. The 10% weight loss temperature (T-10) values of (co)polycarbonates, determined by thermogravimetric analysis under nitrogen atmosphere, were in the range 427-438 degrees C indicating their good thermal stability. The glass transition temperature (T-g) values of (co)polycarbonates were observed in the range 147-152 degrees C. The crosslinking ability of (co)polycarbonates involving pendant propargyloxy groups leading to formation of networked structure was evaluated via non-isothermal curing studies by DSC. As a proof-of-concept, the post-modification of a representative polycarbonate bearing pendant propargyloxy groups with 1-octane thiol as a model compound via thiol-yne click reaction was briefly studied.
Keywords: Aromatic polycarbonate; Chemical modification; propargyloxy groups; thermal crosslinking; thiol-yne click reaction

Post-polymerization modifiable aromatic (co)poly(ether sulfone)s possessing pendant norbornenyl groups based upon a new bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (European Polymer Journal, 2022)
A new bisphenol possessing pendant norbornenyl group viz., 4, 4 `-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was synthesized by a single-step base-catalyzed condensation reaction of 5-norbor-nene-2-carboxaldehyde with guaiacol. NMR spectral data indicated formation of BPA-NB comprising of isomeric components. A series of (co)poly(ether sulfone)s possessing pendant norbornenyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar ratio of BPA-NB and bisphenol-A (BPA) with bis(4-fluorophenyl) sulfone. Inherent viscosity values and number average molecular weights of (co)poly (ether sulfone)s were in the range 0.67-1.01 dL/g and 75,400-1,16,300 g/mol, respectively indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)poly(ether sulfone)s. (Co)poly(ether sulfone)s were characterized using FT-IR, H-1 NMR and C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The formation of random copoly(ether sulfone)s was demonstrated by( 13)C NMR analysis. The incorporation of BPA-NB into (co)poly(ether sulfone)s resulted into improvement in Tg values. BPA-NB-based (co)poly(ether sulfone)s offered possibilities for post -modifications involving either methoxyl or norbornenyl groups. A representative copoly(ether sulfone) (PSU-NB-2) possessing pendant norbornenyl groups was chemically modified via thiol-ene reaction with three representative thiol compounds, namely, 1-dodecanethiol, 2-furanmethanethiol and 2-mercaptoethanol to yield corresponding post-modified polymers in a quantitative manner. Additionally, it was demonstrated that copoly (ether sulfone) possessing pendant norbornenyl groups could be used to form insoluble cross-linked gel in the presence of a multifunctional thiol cross-linker.
Keywords: (Co)poly(ether sulfone)s; bisphenol; Cross -linking; Pendant norbornenyl groups; Thiol-ene reaction

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking

Norbornenyl-pendant aromatic (co)poly(ether ether ketone)s - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (Journal of macromolecular science part A- pure and applied chemistry, 2023)
4, 4'-(Bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was utilized as a step-growth monomer for the synthesis of (co)poly(ether ether ketone)s (PEEK-NBs) via nucleophilic aromatic substitution polycondensation. A homo and five PEEK-NBs were synthesized by polycondensation of 4, 4'-difluorobenzophenone with BPA-NB and various compositions of BPA-NB and bisphenol-A, respectively. H-1 NMR spectroscopy confirmed the chemical structure and composition of PEEK-NBs. Inherent viscosity and number-average molecular weight values of PEEK-NBs were in the range 0.64 to 0.78 dL g(-1) and 62,670 to 84,470 g mol(-1), respectively, indicating the formation of polymers of reasonably high molecular weight. It was easy to dissolve PEEK-NBs in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran. Tough, transparent, and flexible films of PEEK-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated amorphous nature of PEEK-NBs. Glass transition temperature (T-g) values, determined by DSC analysis, of PEEK-NBs were in the range 163 to190 degrees C and T-g values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PEEK-NB was demonstrated using two azido compounds, namely, 4-(azidomethyl)-7-methoxy-2H-chromen-2-one and 9-(azidomethyl)anthracene, via metal-free azide-alkene 1,3-dipolar cycloaddition reaction to obtain copoly(ether ether ketone)s appended with coumarinyl and anthracenyl moieties, respectively.
Keywords: (Co)poly(ether ether ketone)s; azide-alkene click reaction; norbornenyl groups; post-polymerization modification

Aromatic (co)polycarbonates bearing pendant 2,3-dimethylmaleimido group based upon a new phthalimidine-containing "cardo" bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
A new ``cardo'' bisphenol viz., 1-(2-(1,1-bis(4-hydroxyphenyl)-3-oxoisoindolin-2-yl)ethyl)-3,4-dimethyl- 1H-pyrrole-2,5-dione (PPH-MA) was synthesized in a two-step reaction sequence starting from phenolphthalein. PPH-MA was utilized as a step-growth monomer for the synthesis of a homo- and fourco-polycarbonates bearing pendant 2,3-dimethylmaleimido groups (PC-MAs) via solution polycondensation of PPH-MA or various mol % compositions of PPH-MA and bisphenol-A, respectively, with triphosgene.H-1 NMR spectroscopy confirmed the chemical structure and composition of PC-MAs. Inherent viscosity and number average molecular weight values of PC-MAs were in the range 0.45-0.64 dL g(-1) and 18,300 - 36,200 g mol(-1), respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent and flexible films of PC-MAs could be cast from chloroform solution. X-ray diffraction studies indicated the amorphous nature of PC-MAs. The 10% weight loss temperature (T-10) values of PC-MAs were in the range 373-443 degrees C indicating their good thermal stability.
Keywords: (co)polycarbonates; 2; 3-dimethylmaleimido; phenolphthalein; phthalimidine ring; ``cardo'' bisphenol

Aromatic (Co)polycarbonates bearing pendant norbornenyl groups: Synthesis, characterization and post-polymerization modification - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (High Performance Polymers, 2024)
A homo- and three co-polycarbonates (PC-NBs) bearing pendant norbornenyl groups were synthesized via solution polycondensation of triphosgene with 4, 4'-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) or various mol % compositions of BPA-NB and bisphenol-A, respectively. 1H-NMR spectroscopy confirmed the chemical structure and composition of PC-NBs. Inherent viscosity and number-average molecular weight (Mn) values of PC-NBs were in the range 0.44 - 0.64 dL g-1 and 21,800 - 34,100 g mol-1, respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent, and flexible films of PC-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated the amorphous nature of PC-NBs. Glass transition temperature (Tg) values, determined by DSC analysis, of PC-NBs were in the range 154 - 175 degrees C and Tg values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PC-NB was demonstrated using 3,6-diphenyl-1,2,4,5-tetrazine via tetrazine-ene reaction.
Keywords: (co)polycarbonates; norbornenyl groups; post-polymerization modification; tetrazine-ene click reaction; thermoplastics

Synthesis and characterization aromatic copolyesters bearing pendant norbornenyl groups - Talanikar, Aniket A.; Bhong, Sahil T.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (High Performance Polymers, 2026)
4, 4'-(Bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was polymerized via phase transfer catalyzed interfacial polycondensation with an equimolar mixture (50:50 mol %) of isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC) to obtain aromatic copolyester bearing pendant norbornenyl groups (PES-NB). Furthermore, three different compositions of BPA-NB and bisphenol A (BPA) were polycondensed with IPC to obtain a series of copolyesters. 1H NMR spectroscopy confirmed the chemical structure and compositions of PES-NBs. Inherent viscosity and number-average molecular weight values of PES-NBs were in the range 0.82 to 1.06 dLg-1 and 63,600 to 95,300 gmol-1, respectively, indicating the formation of polymers of reasonably high molecular weights. PES-NBs readily dissolved in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran, and tough, transparent, flexible films could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of PES-NBs. Glass transition temperature (Tg) values of PES-NBs were in the range 215 to 195 degrees C and Tg values increased with the increase in mol % of BPA-NB.
Keywords: aromatic (co)polyesters; glass-transition temperature (Tg); interfacial polycondensation; norbornenyl groups